Local Control of the Bureaucracy: Federal Appeals Courts, Ideology, and the Internal Revenue Service - Robert M. Howard; David C. Nixon (Washington University Journal of Law & Policy, 2003)
Recent studies show that the IRS is subject to some political control in shifting its policy between competing ideological or partisan concerns. We extend these studies to examine regional court influence over IRS audit policy within the separation of powers (“SOP”) framework. Examining cross-sectional time series data from 1960 until 1988, we found that the IRS shifts the number of audits it conducts of businesses versus individuals in response to the prevailing median ideology of the federal courts of appeals, and in response to the prevailing ideological framework of the President and Congress. As the median federal court of appeals judge in a circuit becomes more liberal, the IRS conducts more audits of businesses located in that region. As the median federal court of appeals judge in a circuit becomes more conservative, the IRS conducts more audits of individuals living in that region. Courts, therefore, provide an additional measure of control over bureaucratic behavior. The different ideologies of the various courts of appeals provide an explanation for regional variation in IRS policy.
Keywords: Tax auditing; Separation of powers; Social science research; Ideology; United States. Court of Appeals; United States. Internal Revenue Service